THE LEGAL IMPLICATIONS OF SIGNING THE UNWTO FRAMEWORK CONVENTION ON TOURISM ETHICS FOR THE SUSTAINABLE TOURISM DEVELOPMENT IN INDONESIA - Laksmidewi, Cok Dian (UNISSULA, 2022)
Indonesia's international relations in the world association have implications for its commitment to participate in various global issues, including tourism. The UNWTO Framework Convention on Tourism Ethics is an international agreement made to reorganize tourism business ethics. In this study, there are two issues discussed, namely Indonesia's engagement in The UNWTO Framework Convention on Tourism Ethics and tourism business ethics in the perspective of human rights. Indonesia became the first country to sign the UNWTO Framework Convention on Tourism Ethics. Normatively, the signing of this international agreement is followed by the deposit of the instrument of ratification, acceptance or approval stating the State's approval to be bound by the treaty at the international level. Indonesia's engagement in The UNWTO Framework Convention on Tourism Ethics signifies Indonesia's commitment to rebuild tourism based on business ethics. The business ethics in sustainable tourism development will be oriented to the fulfillment of human rights. Ratification of this convention places a legal obligation on States to promote responsible and sustainable tourism development, conserve the cultural and natural tourism resources of destinations, protect local communities and ensure a responsible, sustainable and universally accessible sector.